Pencitraan Publik Sekolah - Maratush Sholikhah (Prodi Manajemen Pendidikan Islam STAI Darussalam, 2021)
Abstract. The educational environment is everything that exists and occurs in the educational process, because the group of objects or the educational environment participates in efforts to develop itself. In this case, educational management, especially in Public Relations management, by paying attention to the human environment, namely a community with quality education. To create a harmonious situation and conditions between the school management and the community, simultaneous and comprehensive cooperation and contact between the two parties is needed. The school's public image is a very appropriate step in creating harmonious conditions between the management and the community. Kotler (1995) broadly defines image as the number of beliefs, images, and impressions that a person has on an object. The object in question can be a person, organization, group of people or anything else that he knows. If the object is an organization, it means that all beliefs, images and impressions of a person's organization are images.